2021
DOI: 10.1302/2633-1462.26.bjo-2021-0025.r1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Exeter V40 femoral stem prosthesis fracture

Abstract: Aims The Exeter V40 cemented polished tapered stem system has demonstrated excellent long-term outcomes. This paper presents a systematic review of the existing literature and reports on a large case series comparing implant fractures between the Exeter V40 series; 125 mm and conventional length stem systems. Methods A systematic literature search was performed adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. In parallel, we performed a retrospective single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…By using data from the NJR, they identified 2,158 primary THA employing this implant and found a revision risk that was nearly double that observed with the standard Exeter ® stem at 10-years follow-up [ 10 ]. Periprosthetic fracture was one of the largest contributors to the revision of the SRS stem [ 10 ], which is consistent with the increased risk associated with the collarless polished taper slip design [ 24 , 25 ]. A systematic review by Thompson et al [ 24 ] found 25 reported cases of prosthetic fractures of Exeter ® stems and demonstrated that short (125 mm) stem length was more likely to fracture, and of the seven reported short stems, four were SRS (44/00/125).…”
Section: Discussionmentioning
confidence: 71%
“…By using data from the NJR, they identified 2,158 primary THA employing this implant and found a revision risk that was nearly double that observed with the standard Exeter ® stem at 10-years follow-up [ 10 ]. Periprosthetic fracture was one of the largest contributors to the revision of the SRS stem [ 10 ], which is consistent with the increased risk associated with the collarless polished taper slip design [ 24 , 25 ]. A systematic review by Thompson et al [ 24 ] found 25 reported cases of prosthetic fractures of Exeter ® stems and demonstrated that short (125 mm) stem length was more likely to fracture, and of the seven reported short stems, four were SRS (44/00/125).…”
Section: Discussionmentioning
confidence: 71%
“…Even in two large series, in which the rate of revision surgery due to V40 taper problems was analyzed, a detailed description of ALTR is either lacking or restricted to revised cases. Thompson et al, 39 who found an incidence of 0.15% and 1.21% for taper fractures in 5,370 primary and 662 revision THAs involving Exeter V40 femoral components, did not report follow-up investigations in the patients who did not have a fractured taper. Urish et al 19 reported an incidence of 4.7% of gross trunnion failure and head-neck taper corrosion with LFIT CoCr heads (Stryker) and Accolade TMZF components in 636 patients, but did not perform additional investigations in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al. found the short Exeter stems had a higher rate of fracture than the standard Exeter stems in their unit (1.25% vs 0.15%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%